2016
DOI: 10.1002/jbm.a.35794
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of two perfusion routes with different flow in decellularization to harvest an optimal pulmonary scaffold for recellularization

Abstract: Decellularization processes may variably distort or degrade extracellular matrix (ECM) structure. In this study, two perfusion routes (PR) were tested on SD rat lung samples. One decellularization protocol, PR1, was perfused through the pulmonary artery. The other decellularization protocol, PR2, was perfused through the trachea. Both decellularization protocols were used by the same detergent-based (sodium dodecyl sulphate and Triton X-100) with different flow continuous perfusion. There was no visible differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…Both protocols demonstrated preserved alveolar septum and visceral pleura, which are important pulmonary structures that determine optimum decellularized lungs, similar to the previous results. Wang et al, 2016 [ 9 ], recently compared the same routes for lung decellularization, the trachea and pulmonary artery, and demonstrated preserved ECM, but the airway structure and alveoli architecture of the pulmonary decellularized lung was partially destroyed. This probably occurred because of the high flow applied in the pulmonary artery during the decellularization process, unlike the constant physiological pressure applied in our protocol, which maintained the lung structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both protocols demonstrated preserved alveolar septum and visceral pleura, which are important pulmonary structures that determine optimum decellularized lungs, similar to the previous results. Wang et al, 2016 [ 9 ], recently compared the same routes for lung decellularization, the trachea and pulmonary artery, and demonstrated preserved ECM, but the airway structure and alveoli architecture of the pulmonary decellularized lung was partially destroyed. This probably occurred because of the high flow applied in the pulmonary artery during the decellularization process, unlike the constant physiological pressure applied in our protocol, which maintained the lung structures.…”
Section: Discussionmentioning
confidence: 99%
“…The agents for lung decellularization can be applied by using two different infusion routes: the pulmonary vasculature and the airway tree [ 9 ]. A previous study from our group demonstrated that decellularization process by both routes did not induce any significant differences in the micro-scale local stiffness of the decellularized lung [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lung, however, has an additional possible route for decellularization since the detergents can also be infused through the trachea. In fact, both routes (trachea and pulmonary artery) alone or combined have been used to effectively decellularize lungs (Price et al, 2010;Maghsoudlou et al, 2013;Tsuchiya et al, 2016;Wang et al, 2016). By using an intermittent intra-tracheal flow of detergent for decellularization, the same combination of SDC/Triton X-100 yielded an acellular scaffold in a shorter time FIGURE 2 | ECM decomposition and reconstruction after recellularization.…”
Section: Change Of Decellularization Proceduresmentioning
confidence: 99%
“…Both SDS and Triton X-100 have been commonly used as detergents for cell lysis applications in TE. Notably, studies have demonstrated that perfusion decellularization protocols have been commonly performed on relatively large organs with distinct blood vessels or catheters, such as kidneys and lungs [ 14 , 16 ]. More so, in tissues where blood vessels hardly separate like in small intestine submucosa (SIS) and testis tissues, immersion/agitation decellularization could be an alternative option [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%